Processes, actors and ideas in the debate on the international insertion of Argentina (with some references to Chile), 1850-1914 - Hora, Roy (Revista de Historia Social y de las Mentalidades, 2024)
This essay analyses some features of Argentina’s integration into the world markets during the export-led era, c. 1850-1914. It focuses on the forces that shaped Argentina’s export led growth, explores the debates it raised and the actors that promoted and took advantage of this process. Contrasts with the Chilean experience help to shighlight some peculiarities of the case under study.